Development of Organic Agriculture in the European Union Member States: The Role of Public-Private Partnership - POLUSHKINA, Tatyana Mikhailovna; AKIMOVA, Yulia Alekseevna; KOROLEVA, Tatyana Petrovna; KOCHETKOVA, Svetlana Andreevna; ZININA, Lyubov Ivanovna (Journal of Environmental Management and Tourism, 2020)
This study focuses on the need to use public-private partnership (PPP) mechanisms in the development of organic agriculture in order to solve problems in the field of sustainable rural development, when economic well-being is achieved not through the environmental degradation that threatens human life and health, and especially the health of future generations, but in harmony with nature; and to improve food security of the country in the field of providing quality nutrition. The conclusion has been made that it is important and necessary to develop organic agriculture in the modern Russia to increase the sustainability of its development. The analysis of global trends in the development of the organic sector of agricultural production has been carried out. A review of the practice of applying PPP mechanisms in the development of this agricultural sector in Europe has been provided. The conclusion about PPP as an effective tool for bringing relations between agricultural organizations and the state to a new level has been justified, which will help create an efficient mechanism for updating fixed assets and, therefore, increase the level of agricultural production.